Potential Application of Quantitative Prostate-specific Antigen Analysis in Forensic Examination of Seminal Stains - Zhenping Liu; Yang Yang; Zhikan Pan; Xiaoxu Zhu; Shi Feng; Dong Zhao (Wolters Kluwer Medknow Publications, 2015)
The aims of this study are to use quantitative analysis of the prostate-specific antigen (PSA) in the seminal stain examination and to explore the practical value of this analysis in forensic science. For a comprehensive analysis, vaginal swabs from 48 rape cases were tested both by a PSA fluorescence analyzer (i-CHROMA Reader) and by a conventional PSA strip test. To confirm the results of these PSA tests, seminal DNA was tested following differential extraction. Compared to the PSA strip test, the PSA rapid quantitative fluorescence analyzer provided the more accurate and sensitive results. More importantly, individualized schemes based on quantitative PSA results of samples can be developed to improve the quality and procedural efficiency in the forensic seminal inspection of samples prior to DNA analysis.